MiDAS: the field guide to the microbes of activated sludge. (27th June 2015) - McIlroy, Simon Jon; Saunders, Aaron Marc; Albertsen, Mads; Nierychlo, Marta; McIlroy, Bianca; Hansen, Aviaja Anna; Karst, Søren Michael; Nielsen, Jeppe Lund; Nielsen, Per Halkjær
Abstract: The Microbial Database for Activated Sludge (MiDAS) field guide is a freely available online resource linking the identity of abundant and process critical microorganisms in activated sludge wastewater treatment systems to available data related to their functional importance. Phenotypic properties of some of these genera are described, but most are known only from sequence data. The MiDAS taxonomy is a manual curation of the SILVA taxonomy that proposes a name for all genus-level taxa observed to be abundant by large-scale 16 S rRNA gene amplicon sequencing of full-scale activated sludge communities. The taxonomy can be used to classify unknown sequences, and the online MiDAS field guide links the identity to the available information about their morphology, diversity, physiology and distribution. The use of a common taxonomy across the field will provide a solid foundation for the study of microbial ecology of the activated sludge process and related treatment processes. The online MiDAS field guide is a collaborative workspace intended to facilitate a better understanding of the ecology of activated sludge and related treatment processes—knowledge that will be an invaluable resource for the optimal design and operation of these systems. Database URL: http://www.midasfieldguide.org